Evaluation of the efficiency of anaerobic reactors in the removal of pollutants from fish processing effluents - Sampaio, R. R. [UNESP]; Sousa, S. R. [UNESP]; Rodrigues, L. S.; Silva, I. J. (FapUNIFESP (SciELO), 2022)
The objective of the present work was to evaluate the performance of a compartmentalized anaerobic reactor (CAR) followed by anaerobic filter in real scale, effluent treatment from fish fridge processing. The work was developed in a fish fridge located in the south of the state of Minas Gerais, which has an effluent treatment plant composed of static screen, grease removal device, CAR reactor and anaerobic filter. The monitoring happened trough physical-chemical parameters of fluids and effluents from all sampling points of the plant biweekly. The parameters evaluated were temperature, pH, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), volatile suspended solids (VSS), volatile fatty acids (VFA) and alkalinity. Operational problems found in the primary treatment were not limiting for the system performance, which managed to meet the parameters of environmental legislation in Minas Gerais according to the efficiency of removal of COD, BOD and VSS from wastewater from fish processing
Avaliação da eficiência de reatores anaeróbios na remoção de poluentes em efluentes do processamento de pescado
Keywords: Agroindustry; Anaerobic digestion; Environmental impact